1991
DOI: 10.1115/1.2891236
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Knee Motion and External Loading on the Length of the Anterior Cruciate Ligament (ACL): A Kinematic Study

Abstract: A six-degrees-of-freedom mechanical linkage device was designed and used to study the unconstrained motion of ten intact human cadaver knees. The knees were subjected to externally applied varus and valgus (V-V) moments up to 14 N-m as well as anterior and posterior (A-P) loads up to 100 N. Tests were done at four knee flexion angles; 0, 30, 45, and 90 deg. Significant coupled axial tibial rotation was found, up to 21.0 deg for V-V loading (at 90 deg of flexion) and 14.2 deg for A-P loading (at 45 deg of flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
66
2
5

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(84 citation statements)
references
References 0 publications
11
66
2
5
Order By: Relevance
“…The effects of ACL transection on these findings were again dependent on constraint: in the constrained state the valgus range increased by 10%, but by 186% when unconstrained, and both valgus and varus were coupled with anterior translation. These results are corroborated by those of Hollis et al (1991), who found coupled internal and external rotation with applied valgus and varus torques, respectively.…”
Section: Valgus Rotationsupporting
confidence: 82%
See 2 more Smart Citations
“…The effects of ACL transection on these findings were again dependent on constraint: in the constrained state the valgus range increased by 10%, but by 186% when unconstrained, and both valgus and varus were coupled with anterior translation. These results are corroborated by those of Hollis et al (1991), who found coupled internal and external rotation with applied valgus and varus torques, respectively.…”
Section: Valgus Rotationsupporting
confidence: 82%
“…When the knees were constrained to move only in anterior translation the measured translation was substantially less. In other cadaveric studies, application of a 100N anterior force produced coupled internal rotation (Hollis et al, 1991), and simulated 200N quadriceps contraction caused anterior tibial translation coupled with internal rotation (Li et al, 1999). Internal rotation due to anterior force is not a universal finding, with Lo et al (2008) showing a 50N anterior force (with a 100N joint compressive force) did not elicit a significant increase in rotation.…”
Section: Combined Anterior Translation/internal Rotationmentioning
confidence: 83%
See 1 more Smart Citation
“…Several authors have focused on ligament kinematic behaviour with the aim to support ligament injury treatment: ACL and PCL elongation was investigated ex vivo [10,11] and in vivo [12][13][14]. Fewer studies have dealt with the MCL and LCL [15].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical linkage systems incorporate six degrees-of-freedom (6 joints) and use potentiometers or optical encoders to measure position of linkage joints and determine the end-to-end position and orientation (Chao, et al, 1980;Gardner, et al, 1996;Hollis, et al, 1991;Kinzel, et al, 1972;McClure, et al, 1998;Townsend, et al, 1977). 3 Mechanical linkages can achieve sub-millimeter accuracy, but the measurement space (linkage reach) tends to be limited to about 50 cm.…”
mentioning
confidence: 99%